2019
DOI: 10.1108/afr-01-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to participate and pay for index-based crop insurance in Ghana

Abstract: Purpose The purpose of this paper is to assess farmers’ willingness to participate and pay for weather-based index insurance in the Upper East Region of Ghana, and what factors influence the participation and purchase of crop insurance schemes. Design/methodology/approach A survey of 200 farmers in the region was carried out in 2018 to measure demographic information, farm characteristics, risks and risk-management practices and attitudes to crop insurance programs. The survey also captured maximum willingne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 35 publications
5
20
1
Order By: Relevance
“…The value of ATnormalE1 (0.642) suggests that not all the exposed farmers accessed credit from rural banks. This finding is consistent with Adjabui et al (2019), who assessed the willingness of farmers to participate and pay for index-based crop insurance in Ghana and found that some farmers did not take up the crop insurance for several reasons, including farmers’ attitude toward crop insurance.…”
Section: Resultssupporting
confidence: 88%
“…The value of ATnormalE1 (0.642) suggests that not all the exposed farmers accessed credit from rural banks. This finding is consistent with Adjabui et al (2019), who assessed the willingness of farmers to participate and pay for index-based crop insurance in Ghana and found that some farmers did not take up the crop insurance for several reasons, including farmers’ attitude toward crop insurance.…”
Section: Resultssupporting
confidence: 88%
“…(4) In the Italian agricultural insurance system there is not a positive relationship between a farmer's educational background and insurance diffusion. Our result is consistent with Black and Dorfman (2000), Velandia et al, (2009) and Adjabui et al (2019) who, in their studies found a negative relationship between education and crop insurance adoption, but contrasts with those who found a positive relationship between education and crop insurance (Sherrick et al, 2004;Olubiyo et al, 2009;Cole et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Although agricultural insurance has been discussed for more than 3 decades, with various studies covering accessibility [3,11,16], acceptability [12,17] and willingness to pay for agricultural insurance [18][19][20], the dedicated literature on agricultural insurance covering the global south and particularly Ghana remains scanty. Even with the few studies that focused on Ghana, they remained largely skewed towards northern Ghana [18,21]. Choudhary and D' Alessandro [22] indicated the most studies focused on Northern Ghana because it constitutes a region that is most prone to climate variability (floods, droughts, intense sunlight).…”
Section: Introductionmentioning
confidence: 99%